2019
DOI: 10.1159/000500707
|View full text |Cite
|
Sign up to set email alerts
|

Habitual Alcohol Intake Modifies Relationship of Uric Acid to Incident Chronic Kidney Disease

Abstract: Background: Previous studies showed that higher serum uric acid levels increased the risk of chronic kidney disease (CKD), but moderate alcohol consumption decreased it. The comparative importance of serum uric acid levels and habitual alcohol consumption as risk factors for CKD remain undefined. We therefore evaluated the relationship of baseline serum uric acid level in combination with daily alcohol consumption to the incidence of CKD. Methods: A prospective cohort study of 9,116 middle-aged nondiabetic ­Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Further, alcohol consumption leads to hyperuricemia as a result of the high purine content of certain types of alcoholic beverages, 13 increased urate production from purine nucleotide degradation during ethanol catabolism, and lactic acid inhibition of renal urate excretion 13 . However, to the best of our knowledge, few studies have examined the interactive effects of alcohol consumption and SUA levels on renal dysfunction in Japanese populations 14 …”
Section: Introductionmentioning
confidence: 99%
“…Further, alcohol consumption leads to hyperuricemia as a result of the high purine content of certain types of alcoholic beverages, 13 increased urate production from purine nucleotide degradation during ethanol catabolism, and lactic acid inhibition of renal urate excretion 13 . However, to the best of our knowledge, few studies have examined the interactive effects of alcohol consumption and SUA levels on renal dysfunction in Japanese populations 14 …”
Section: Introductionmentioning
confidence: 99%
“…The China Kadoorie Biobank reported that 8% of males are drinkers and individuals engaging in heavy drinking episodes were likely to have multiple risk factors such as regular smoking, low physical activity, and hypertension [ 7 ]. Various diseases including diabetes, chronic kidney disease (CKD), and ischemic stroke are associated with heavy alcohol intake in the Chinese population [ 8 , 9 ]. Although drinking behaviors vary over time in China, there is emerging evidence that defines the potential correlation of the changing drinking behaviors with the development of HUA.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 34 publications selected, the present meta-analysis finally included 12 publications [ 19 , 20 , 21 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ] from 11 cohort studies ( N = 14,634,940), including the Physicians’ Health Study (PHS) study which defined the outcome as eGFR of <55 mL/min [ 32 ]. We excluded 23 publications because two publications were cross-sectional studies [ 41 , 42 ], two did not assess alcohol consumption (g/day) as a predictor of proteinuria and/or low GFR [ 43 , 44 ], three categorized alcohol consumption into only two levels (none vs. ≥1 drink/day [ 45 ], no use vs. use of alcohol [ 46 ], and alcohol consumption of <20 vs. ≥20 g/day [ 47 ]), four did not stratify current drinkers by alcohol consumption level (g/day) [ 48 , 49 , 50 , 51 ], one had the highest alcohol consumption category with the lower boundary of <12 g/day, [ 52 ] one had a sex-specific definition of alcohol consumption level [ 53 ], one did not define the outcome of CKD [ 54 ], seven did not have the outcome of incidence of proteinuria or low GFR [ 55 , 56 , 57 , 58 , 59 , 60 , 61 ], one had missing information on the number of participants of alcohol consumption categories [ 62 ], and one reported similar results in previous publications [ 63 ].…”
Section: Resultsmentioning
confidence: 99%